A practical fluorescence-based screening protocol for polyethylene terephthalate degrading microorganisms - Chaves, Michel R. B.; Lima, Maria L. S. O.; Malafatti‑Picca, Lusiane [UNESP]; De Angelis, Derlene A.; De Castro, Aline M.; Valoni, Érika; Marsaioli, Anita J. (Sociedade Brasileira de Quimica (SBQ), 2018)
We propose a practical, low-cost and selective fluorescence-based protocol adapted to identify polyethylene terephthalate (PET) degrading microorganisms. The microbial hydrolysis of PET nanoparticles was monitored by 2-hydroxyterephthalate, a fluorophore produced in situ after radical hydroxylation of terephthalic acid (TPA), the final hydrolysis product, by the Fenton reaction. Seven fungi presenting promising PET hydrolytic potential using the proposed microscale screening assay were identified. The strains evaluated presented a substantial increase of up to 18-fold in PET nanoparticles conversion, such as obtained by the fungus Trichoderma sp. C70, after their cultivation in a PET-enriched medium. The formation of other hydrolysis products, along with TPA, was observed using matrix assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS).
Keywords: Biocatalysis; Fenton reaction; Fluorescence; Microorganism screening; PET degradation